Covalent Organic Frameworks: Covalent Organic Frameworks: Structures, Synthesis, and Applications (Adv. Funct. Mater. 33/2018). (13th August 2018) - Lohse, Maria S.; Bein, Thomas
Abstract : In article number 1705553, Thomas Bein and co‐workers provide a comprehensive overview of the covalent organic framework structures realized to date. Advanced synthesis strategies are discussed, as well as applications, which include gas storage, sensing, electrochemical energy storage, and optoelectronics.